Réponses

2013-05-01T10:37:36+02:00

2x+7= -9
2x = -9 -7
2x = -16
x = -16 / 2 
x= -8

-4x - 1 = 11
- 4x = 11+1
- 4x = 12
-x = 12 / 4
x = - 3


 

 

Meilleure réponse !
2013-05-01T10:43:14+02:00

2x + 7 = -9

2x + 7 - 7 = - 9 - 7                    J'enlèves 7 dans chaque membre et je divises par 2 pour trouver x

2x = - 16

2x / 2 = -16 / 2

x = -8

 

-4x - 1 = 11

-4x - 1+ 1 = 11 + 1

-4x / -4 = 12 / -4

x = - 3

 

3x - 5 = -2

3x - 5 + 5 = -2 + 5

3x / 3 = 3 / 3

x = 1

 

- 5x + 4 = 2

- 5x + 4 - 4 = 2 - 4

-5x / -5 = -2 / -5

x = 2/5

 

x/2 + 3 = 0

x/2 + 3 - 3 = 0 - 3

x/2 = -3

x/2 *2 = -3*2

x = -6